Utilization of a Chimeric Medial Femoral Condyle Free Flap for Mandibular Osteoradionecrosis - Kongkrit Chaiyasate, MD; Rohun Gupta, BA; Jithin John, BS; Sean Chaiyasate; Jeremy Powers, MD; Alan Nguyen, BS; Christopher Issa, BS; Justin Hart, DO; Joshua J. Goldman, MD; Neil S. Sachanandani, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. Primary options for oromandibular reconstruction with osteocutaneous free flaps are the vascularized fibula and iliac crest. Complications of mandible reconstruction are not uncommon and include osteomyelitis, malunion, and osteoradionecrosis (ORN) after radiation therapy. The medial femoral condyle (MFC) free flap is an established salvage option for carpal reconstruction in hand surgery, frequently used for scaphoid nonunion and avascular necrosis. We hypothesize that the MFC flap can be utilized to restore blood supply and reverse the negative effects of radiotherapy in patients who require mandibular reconstruction due to ORN. Methods:. A retrospective chart review was conducted at Beaumont Health System, Royal Oak, for patients who underwent MFC free flap reconstruction for mandibular ORN between the years 2012 and 2018. Demographic data, operative details, complications, medical comorbidities, and patient outcomes were retrospectively gathered. Results:. A total of four patients were isolated. Four patients developed ORN after resection of squamous cell carcinoma and adjuvant radiotherapy. No patients experienced donor site deficits. Revisions after MFC reconstruction were dependent on individual aesthetics and involvement of neighboring tissue. All four patients continue to be followed with no current issues to the osseous component of the MFC flap. Conclusion:. Utilization of the MFC periosteal flap is a viable option in selected patients to salvage nonunion/resorption of mandible reconstruction and ORN of the mandible. Our experience found that the MFC is able to provide pain resolution and healing of intraoral soft tissue defects, and may halt the progression of ORN of the mandible.